The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.media.2019.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Not-so-supervised: A survey of semi-supervised, multi-instance, and transfer learning in medical image analysis

Abstract: Machine learning (ML) algorithms have made a tremendous impact in the field of medical imaging. While medical imaging datasets have been growing in size, a challenge for supervised ML algorithms that is frequently mentioned is the lack of annotated data. As a result, various methods that can learn with less/other types of supervision, have been proposed. We give an overview of semi-supervised, multiple instance, and transfer learning in medical imaging, both in diagnosis or segmentation tasks. We also discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
441
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 720 publications
(474 citation statements)
references
References 150 publications
5
441
0
1
Order By: Relevance
“…Yi et al (2018) broadly investigated the use of GANs in medical imaging. Cheplygina et al (2019) reviewed semi-supervised, multi-instance learning, and transfer learning in medical image analysis, covering both deep learning and traditional segmentation methods. Hesamian et al (2019) surveyed deep learning techniques suggested for medical image segmentation but with a particular focus on architectural advancements and training schemes.…”
Section: Related Workmentioning
confidence: 99%
“…Yi et al (2018) broadly investigated the use of GANs in medical imaging. Cheplygina et al (2019) reviewed semi-supervised, multi-instance learning, and transfer learning in medical image analysis, covering both deep learning and traditional segmentation methods. Hesamian et al (2019) surveyed deep learning techniques suggested for medical image segmentation but with a particular focus on architectural advancements and training schemes.…”
Section: Related Workmentioning
confidence: 99%
“…A powerful property of disentangled representations is that they can be applied in semi-supervised learning [Almahairi et al, 2018]. An important application in medical image analysis is (semi-supervised) segmentation, for a recent review see Cheplygina et al [2018]. As discussed in this review, manual segmentations are a laborious task, particularly as inter-rater variation means multiple labels are required to reach a consensus, and images labelled by multiple experts are very limited.…”
Section: Semi-supervised Segmentationmentioning
confidence: 99%
“…First, there are two articles covering visual domain adaptation [24], [25], with a third one specializing in deep learning [26]. Secondly, there is an empirical comparison of domain adaptation methods for genomic sequence analysis [27] and thirdly, a survey paper on, amongst others, transfer learning in biomedical imaging [28].…”
Section: Scopementioning
confidence: 99%